ANALISIS KEMAMPUAN PEMAHAMAN MATEMATIKA DALAM MENYELESAIKAN SOAL SISTEM PERSAMAAN LINEAR TIGA VARIABEL (SPLTV) SISWA KELAS X.IPA MAN 3 AGAM - Rahmatul Yusna; M. Imamuddin; Delniyanti Delniyanti (Universitas Pahlawan Tuanku Tambusai, 2022)
This article was written with the aim of describing the ability to understand mathematics in solving system problems of three variable linear equations (SPLTV) class X.IPA MAN 3 AGAM. This study used a descriptive method with 22 students in class X.IPA as subjects. The instruments used were test sheets and interviews. The result obtained through this study are stedents ability to understand mathematics in solving three-variable linear equation system problems is in the medium category. This is obtained from the analysis of the items carried out on questions that students tend to experience problems with. Of the 3 questions given, most students were able to answer 2 questions. As for 1 more questions, namely the third question in the form of story questions, many were unable to solve it, this was due to the subject’s lack of habit of answering story questions Keywords: Comprehension Ability, Mathematics, System Of Three-Variable Linear Equetions